The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1111/j.1365-2672.2011.04938.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella in liquid egg albumen by antimicrobial bottle coatings infused with allyl isothiocyanate, nisin and zinc oxide nanoparticles

Abstract: Aims:  To develop an antimicrobial bottle coating effective at inhibiting the growth of Salmonella in liquid egg albumen (egg white) and reduce the risk of human Salmonellosis. Methods and Results:  Four‐ounce glass jars were coated with a mixture of polylactic acid (PLA) polymer and antimicrobial compounds containing 100–500 μl allyl isothiocyanate (AIT), 250 mg nisin, 250 mg zinc oxide nanoparticles per jar or their combinations. The coated jars contained 100 ml of liquid egg white (LEW) inoculated with a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Salmonella) [14,15], and that the MIC of AITC against E. coli ranges between 50 and 200 mg/l over 48 h [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella) [14,15], and that the MIC of AITC against E. coli ranges between 50 and 200 mg/l over 48 h [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the PLA coating with 500 μL AIT completely inactivated 3 and 7 log CFU/mL of Salmonella after 7 and 21 days of storage, respectively (Jin & Gurtler, 2011). However, to the best of the authors' knowledge, there are no reported studies combining PEF with antimicrobial bottles.…”
Section: Introductionmentioning
confidence: 96%
“…The incorporation of metal nanoparticles (NPs) into polymer film matrices has been noted as the most promising method of achieving the latter goal. [1][2][3][4][5][6] The NPs offer an antimicrobial ability because of their extremely small particle sizes, which provide an extraordinarily high ratio of surface area to volume or surface area to weight as well as an innumerable number of active surfaces. Zinc oxide (ZnO) has been reported as an interesting potential substance for use in foods in antimicrobial applications.…”
Section: Introductionmentioning
confidence: 99%